Assessment of Caenorhabditis elegans Competitive Fitness in the Presence of a Bacterial Parasite - Penley, McKenna. J. (Bio-Protocol, 2018)

(untitled) (Bio Protoc)
Accurate measurements of an organism’s fitness are crucial for measuring evolutionary change. Methods of fitness measurement are most accurate when incorporating an individual’s survival and fecundity, as well as accounting for any ecological interactions or environmental effects experienced by the organism. Here, we describe a protocol for measuring the relative mean fitness of Caenorhabditis elegans populations, or strains, through an assay that accounts for individual survival, fecundity, and intraspecific competitive ability in the presence of a bacterial parasite. In this competitive fitness assay nematodes from a focal population or strain are mixed with a GFP-marked tester strain in equal proportions, the mixture of nematodes are then exposed to a parasite, and the relative competitive fitness of the focal strain is determined by measuring the change in the ratio of focal nematodes to GFP-marked nematodes after one generation. Specifically, this protocol can be implemented to measure changes in nematode host fitness after experimental evolution by determining the relative competitive fitness of evolved versus ancestral nematode populations.